2015
DOI: 10.14685/rebrapa.v6i1.186
|View full text |Cite
|
Sign up to set email alerts
|

Study of adsorption of lead II in lignin modified from corn waste

Abstract: Resumo: A utilização de metais pesados, principalmente no setor industrial, tem chamado a atenção quanto aos impactos gerados pela utilização de metais potencialmente tóxicos ao meio ambiente e saúde pública. A adsorção é um processo no qual uma substância (adsorvato) é aderida físicamente ou quimicamente à superfície do componente adsorvente e pode ser visto como uma alternativa para a remoção de metais tóxicos. Este trabalho tem o intuito de realizar um estudo sobre a adsorção de Chumbo II (Pb II) em um polí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Similar results were reported by Schafhauser et al (2015) in extractions using the same solvents, in the same order, in maize straw. The authors observed that, at the end of the process, the total percentage of extractives removed was 30.15%.…”
Section: Collection Of Adsorbentssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were reported by Schafhauser et al (2015) in extractions using the same solvents, in the same order, in maize straw. The authors observed that, at the end of the process, the total percentage of extractives removed was 30.15%.…”
Section: Collection Of Adsorbentssupporting
confidence: 88%
“…From each agricultural and agroindustrial residue, hemicelluloses were extracted to obtain a polymer composed of cellulose and lignin, known as a natural adsorbent of maize straw (MS), wheat straw (WT), soybean straw (SS) and soybean hull (SH). The stages of preparation and getting of e natural adsorbents followed the methodology described by Schafhauser et al (2015).…”
Section: Preparation Of Adsorbentsmentioning
confidence: 99%
“…The results showed a variation in adsorption values that can be explained as a function of adsorptive capacity of the used biomass (chemical structure, functional groups) solidification method from lignosulfonate cross-linked with sodium alginate and epichlorohydrin showed an excellent adsorption efficiency (95.6 ± 3.5%) for lead ions at an initial concentration of 25.0 mg L -1 , that suggested the possibility of PLS to be applied for the continuous treatment of wastewater rich in heavy metals at the industry (Li et al, 2015). Schafhauser et al (2015), reported the use of a modified lignin from the corn residue as a lead ion biosorbent, whose removal capacity was 98.87% of an initial solution containing 10 mg.L -1 . According to Zakzeski et al (2010), lignin structure is highly functional and contains alcohol, aldehyde, ether or acid substituents groups.…”
Section: Biosorption Studies Of Pb(ii)mentioning
confidence: 98%
“…The stages of preparation and getting of e natural adsorbents followed the methodology described by Schafhauser et al (2015).…”
Section: Preparation Of Adsorbentsmentioning
confidence: 99%